Beyond the Agrarian Reform Policies in Brazil: An Empirical Study of Brazilian States from 1995 Through 2011 - Sobreiro Filho, José [UNESP]; Mariano, Enzo Barberio [UNESP]; Sobreiro, Vinicius Amorim; Jabbour, Charbel José Chiappetta [UNESP] (Springer Nature, 2016)
The main land reform movements in the world are taking place in Brazil, where various social groups have coordinated their efforts to acquire legal possession of unproductive estates. Although the results achieved over time regarding this dispute are viewed as progress in terms of social inequality, there is no knowledge about the performance of these various movements to date. Based on this context, the main objective of this paper is to evaluate the performance of the Brazilian states and the last four presidential terms in Brazil in minimising social conflicts over land and efficiently converting occupations into settlements.
Keywords: Brazil; Data envelopment analysis (DEA); Land; Performance; Social movements